Prioritisation processes for programme implementation and evaluation in public health: A scoping review - Atwal, Shaileen; Schmider, Jessica; Buchberger, Barbara; Boshnakova, Anelia; Cook, Rob; White, Alicia; El Bcheraoui, Charbel (Frontiers in Public Health, 2023)
Background Programme evaluation is an essential and systematic activity for improving public health programmes through useful, feasible, ethical, and accurate methods. Finite budgets require prioritisation of which programmes can be funded, first, for implementation, and second, evaluation. While criteria for programme funding have been discussed in the literature, a similar discussion around criteria for which programmes are to be evaluated is limited. We reviewed the criteria and frameworks used for prioritisation in public health more broadly, and those used in the prioritisation of programmes for evaluation. We also report on stakeholder involvement in prioritisation processes, and evidence on the use and utility of the frameworks or sets of criteria identified. Our review aims to inform discussion around which criteria and domains are best suited for the prioritisation of public health programmes for evaluation. Methods We reviewed the peer-reviewed literature through OVID MEDLINE (PubMed) on 11 March 2022. We also searched the grey literature through Google and across key websites including World Health Organization (WHO), US Centers for Disease Control and Prevention (CDC), European Centre for Disease Prevention and Control (ECDC), and the International Association of National Public Health Institutes (IANPHI) (14 March 2022). Articles were limited to those published between 2002 and March 2022, in English, French or German. Results We extracted over 300 unique criteria from 40 studies included in the analysis. These criteria were categorised into 16 high-level conceptual domains to allow synthesis of the findings. The domains most frequently considered in the studies were “burden of disease” (33 studies), “social considerations” (30 studies) and “health impacts of the intervention” (28 studies). We only identified one paper which proposed criteria for use in the prioritisation of public health programmes for evaluation. Few prioritisation frameworks had evidence of use outside of the setting in which they were developed, and there was limited assessment of their utility. The existing evidence suggested that prioritisation frameworks can be used successfully in budget allocation, and have been reported to make prioritisation more robust, systematic, transparent, and collaborative. Conclusion Our findings reflect the complexity of prioritisation in public health. Development of a framework for the prioritisation of programmes to be evaluated would fill an evidence gap, as would formal assessment of its utility. The process itself should be formal and transparent, with the aim of engaging a diverse group of stakeholders including patient/public representatives.